CARE PRACTICES PROVIDED BY NURSES OF THE FAMILY HEALTH STRATEGY TO USERS WITH TUBERCULOSIS - Acosta, Daniele Ferreira; Conceição, Pâmela Medina; Abreu, Daiane Porto Gautério; Ramis, Ivy Bastos; Vasconcelos, Stephanie Gonçalves; Soares, Franciele Gomes (Cogitare Enfermagem, 2023)
Objective: to understand the care practices provided by nurses to people with tuberculosis in the Family Health Strategy. Method: descriptive qualitative research, carried out with 11 nurses from family health units in the Rio Grande, RS - Brazil, in the first semester of 2021. The invitation was made by telephone and an online interview was scheduled. The data were analyzed according to content analysis. Results: three categories were evidenced; Practices related to nursing care: obstacles and misconceptions, (Rel)Actions in nursing care for the user with TB, (Re)Thinking about the guidelines provided to the user. The care practices were based on the bond and on welcoming the user. However, there were misunderstandings in the guidelines and obstacles in coping with the disease. A change was observed in the conduct and perception about the disease in the face of the Covid-19 pandemic. Conclusion: good care practices, both relational and technical, are crossed by difficulties, whether internal or external to the unit.